Descriptions of the males of two recently described South African Panurginae (Hymenoptera: Andrenidae), with updated keys to the African species of Melitturga and Meliturgula - Patiny, Sébastien (Zootaxa, 2004)
No updated key to South African Panurginae species has been producedsince the last work of Eardley (1991). In the present paper, descriptions of the unknown sex of 2 recently described species: Melitturga barbareae Eardley, 1991 and Meliturgula eardleyana Patiny, 2000 are provided, along with updated keys taking into account the taxa described since 1991. The biogeographical characteristics of the concerned taxa are also briefly discussed illustrated with maps.